Indigenous Learning: Weaving the Fabric of Our Histories for Success - Angela Hicks; Randy Rowel (Adult Education Research Conference, 2004)
Six public housing community leaders were interviewed for this study. Four themes for recognizing indigenous learning were identified. Themes explained leadership style, validation of and motivation for leadership, and personal impact. The findings give rise to considerations of how adult educators can identify and begin to understand indigenous learning systems.